2019
DOI: 10.1109/access.2019.2902444
|View full text |Cite
|
Sign up to set email alerts
|

STATCOM Model Using Holomorphic Embedding

Abstract: Convergence characteristics of existing Newton-Raphson (N-R) load-flow based FACTS devices models are affected by the choice of initial conditions. Many a time, a solution is either spurious or fails to converge. To overcome the problem of convergence, this paper proposes a holomorphic embedding load-flow method (HELM)-based model of STATCOM. The initial conditions of the proposed model are deterministic and therefore the solution of the model is always unique. The model always converges if the solution exists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
(40 reference statements)
0
16
0
Order By: Relevance
“…From Tables 2 and 3, it can also be verified that the NR based model of STATCOM takes more runtime as compared to NR-assisted FFHE based model of STATCOM and the proposed model also reduces the error at faster rate. In the literature only STATCOM model based on standard HELM has been developed in [24], therefore, the performance of NR-assisted FFHE and basic HELM based model of STATCOM is also investigated. From the various test cases, it has been observed that the FFHE based model of STATCOM takes 80-90% less time and requires 40-70% less terms to converge as compared to basic HELM based model of STATCOM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From Tables 2 and 3, it can also be verified that the NR based model of STATCOM takes more runtime as compared to NR-assisted FFHE based model of STATCOM and the proposed model also reduces the error at faster rate. In the literature only STATCOM model based on standard HELM has been developed in [24], therefore, the performance of NR-assisted FFHE and basic HELM based model of STATCOM is also investigated. From the various test cases, it has been observed that the FFHE based model of STATCOM takes 80-90% less time and requires 40-70% less terms to converge as compared to basic HELM based model of STATCOM.…”
Section: Resultsmentioning
confidence: 99%
“…UPFC is a VSC-based FACTS controller which are more advanced and sophisticated as compared to Thyristor-based FACTS controller because they inject less harmonics, provide independent control, fast dynamic response and higher flexibility. In [24], a VSC-based FACTS controller, namely Static Synchronous Compensator (STATCOM), has been developed as a variable voltage source using standard HELM. However, the presented model of STATCOM requires psn121988@gmail.com (P. Singh); nsenroy@ee.iitd.ac.in (N. Senroy) The remaining part of this paper is organised as follows: Section 2 deals with the methodology used to develop the FFHE based models of STATCOM and UPFC along-with their controlling modes.…”
Section: Introductionmentioning
confidence: 99%
“…• Need of selfcommutating power semiconductor switches. [38], [39] UPFC (unified power flow controller)…”
Section: Ssscmentioning
confidence: 99%
“…In the sphere of HELM, no research work has been found on modeling of Voltage Source Converter (VSC)-based FACTS devices using Holomorphic Embedding (HE) except modeling of Static Synchronous Compensator (STAT-COM) [27]. Therefore, the main aim of this work is to develop the FFHE based models of VSC-based FACTS controllers.…”
Section: Introductionmentioning
confidence: 99%